Assessment of long-term deformation in Johor, Malaysia using Global Positioning System (GPS) and Interferometric Synthetic Aperture Radar (InSAR) - Bin Che Amat, Muhammad Asyran (2017)
Information about deformation in an area has become vital not only for safety assessment but also for maintenance of geodetic infrastructures. The latter is necessary to support accurate surveying and mapping applications. This research exploits the complementary features of Global Positioning System (GPS) and Interferometric Synthetic Aperture Radar (InSAR) techniques to assess the long-term deformation in Johor, Malaysia, which can be induced by natural and/or anthropogenic activities. Furthermore, modelling and mitigation of tropospheric effects in GPS and InSAR are addressed to achieve the best possible precision from the two techniques. Indeed, their modelling and mitigation improve the quality of the estimation as well as provide valuable resources for atmospheric studies. The assessment of long-term deformation in Johor is firstly made by analysing the five years (2007 - 2011) point-specific profile at eight Malaysia Real-Time Kinematic GNSS Network (MyRTKnet) stations. Two processing strategies, namely Precise Point Positioning (PPP) and Double-Difference (DD), are employed to assess their capability for deformation monitoring. The latter also make used of the GPS data from 27 IGb08 stations and 7 International GNSS Service (IGS) stations. Analysis of the results revealed deformation that can be explained by plate tectonic movement and earthquakes in the surrounding region. While results from the PPP processing showed a higher correlation with the recorded earthquakes, the results from DD have improved correlation coefficients at about 4% in the East-West and 5% in the Up-Down components. These improvements are valuable when the rate of deformation is the primary interest. In addition to the point-specific profile, the surrounding deformation of Johor has been assessed with the line-of-sight (LOS) velocity maps from the InSAR time-series. Two sets of ERS-1/2 data, consisting a total of 67 images acquired at two descending tracks (i.e. track 75 and 347), are utilised for the generation of the maps. Moreover, the feasibility of Sentinel-1 satellites is also tested, which revealed improved coherence owing to their short revisit cycle. Some part of Johor showed subsidence and uplift trends, which also agreed with the literature. This information cannot be perceived by the GPS alone due to its limited coverage; hence, further attests to the benefit of their joint analysis. Numerous developments have been implemented in the in-house software (i.e. Punnet) such as the implementation of tropospheric correction, outlier’s rejection scheme, statistical analysis to identify the control point for phase unwrapping, and a new method to retrieve temporal evolution of deformation for a rapidly deforming area.